Penetration rate of takaful Malaysian industry postpandemic of COVID-19 from takaful agents perspective in Shah Alam / Nadia Hanis Ismail - Ismail, Nadia Hanis (2022)
Takaful is an Islamic insurance to insure each other in the event of any loss or damage by contributing money into the group system by each member who subscribes. Takaful branded insurance plan is based on shariah or Islamic law, which describes how individuals are responsible for cooperating and protecting each other. This takaful is halal because it is free from haram elements such as gharar, riba ' and others. Next, this research aim is to study to know the meaning of takaful in more depth in terms of Islam. Apart from that, this paper also examines what is the penetration rate of the post-pandemic Malaysian takaful industry of COVID-19? and also how takaful companies operate and function to assist takaful consumers especially after the Pandemic COVID-19 season? as is well known, now Malaysia and almost one world is hit by Pandemic COVID-19 so this paper aims to find out about in more depth related to the takaful and COVID-19 in terms of takaful agents around Shah Alam, Selangor. After the statistics and information are successfully collected, it will be analysed to evaluate and determine the data.